IMPACT OF CUSTOMER SATISFACTION TOWARDS WORD OF MOUTH IN COMMERCIAL BANK (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This research is designed to analyze the effect of several factors, such as relationship marketing,  service quality, customer satisfaction and word of mouth in the surrounding of  customer in  bank industry.  Survey and explanatory methods are used in the research by applying purposive proportional sampling technique. The technique of data analysis is descriptive, confirmatory factor and structural technique data analysis using Structural equation model ( SEM). The result of validity and reliability test on all items proves that all of those item are valid and reliable. Overall goodness of fit shows that the model used in this research meets the requirement to be a good model. The result of the hypothesis testing on confirmatory factors shows that the estimated factor dimension has signifigant contribution on latent variables among which are relationship marketing,  service quality, customer satisfaction and word of mouth. The result of structural  model hypothesis testing are  as follows : 1) it has been proved that  relationship marketing and service quality have  effect on customer satisfaction. 2) it has been proved that relationship marketing and service quality have  effect on word of mouth. 3) it has been proved that customer satisfaction have  effect on word of mouth. 4) it has been proved that  relationship marketing and service quality have  effect on word of mouth through customer satisfaction.